Mga piling foklor ng Meranao: Isang saling suri - Lomodag, Clarita C. (Animo Repository, 1999)
This study gathers, translates and analyzes the unpublished versions of folk songs, riddles, proverbs and folk tales from the ten municipalities comprising the two districts of Lanao del Sur.The study is an analytical translation of five versions of folk songs, riddles, proverbs and folk tales. The descriptive method of research is used to show the form, differences and similarities of the different folklore versions which are the subject of the study based on lexical and morphological aspects. The narrative structures of the folk tales are also shown.The findings of the study showed that there are lexical differences and similarities in the different folklore examined from the two Lanao districts. The variations are the results of the manner of Maranao life, their beliefs, and geographic location. The start and end of folk tales are similar to the use of words or phrases as, at the time, in the old days, here, since then, and because. The research concluded that there is a great wealth of unpublished Maranao folklore. The narration or whatever form the folklore have been presented, when presented again, will change depending on the character of the presentor and the place where one grew up, as well as the nature of one's language. However, in spite of the differences mentioned, there still remain the fundamental characteristic of narrations, particularly in folklore, like in its customary start and end.